Cash Flow and Profit Impact on Capital Account Liberalization-Investment Growth Nexus in Nigeria: An Aggregated Firm Case - Okungbowa Ewere Florence O. (Economics and Business)
The article examines the firm’s investment growth effect following capital liberalization and financial constraints. It employs firm-level aggregated data of 80 firms for the period of 2006 to 2016. Employing the differenced dynamic panel regression technique, the analysis has revealed among others that investment growth appears to be significantly determined by cash flow (internal), thereby indicating the presence of profound financial constraint among firms in all industries. Second, the capital account liberalization appears to drive investment more through the indirect channel (capital/credit availability channel proxied by cash flow). Third, capital account liberalization-investment growth nexus appears to be less sensitive and significant with high profitability. This could be attributed to “profit flight” or repatriation of profit by foreign investors who may not necessarily prefer ploughing back of profit, which has implication for further expansion of investment among firms. This suggests that the level of capital openness is still low; hence, there is a need for further liberalization of the capital account with some mandate of profit ploughing back.